2016
DOI: 10.1186/s13058-016-0781-6
|View full text |Cite
|
Sign up to set email alerts
|

MCL-1 inhibition provides a new way to suppress breast cancer metastasis and increase sensitivity to dasatinib

Abstract: BackgroundMetastatic disease is largely resistant to therapy and accounts for almost all cancer deaths. Myeloid cell leukemia-1 (MCL-1) is an important regulator of cell survival and chemo-resistance in a wide range of malignancies, and thus its inhibition may prove to be therapeutically useful.MethodsTo examine whether targeting MCL-1 may provide an effective treatment for breast cancer, we constructed inducible models of BIMs2A expression (a specific MCL-1 inhibitor) in MDA-MB-468 (MDA-MB-468-2A) and MDA-MB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 43 publications
6
65
0
1
Order By: Relevance
“…Cyclin E1 was mutated by site-directed mutagenesis as described (18). MDA-MB-468 cells expressing the ecotropic receptor (19) were infected with pMSCV-IRES-GFP retrovirus expressing cyclin E1 wildtype and mutants as described (20). Subpopulations with graded expression of GFP and cyclin proteins were separated by sterile FACS and matched populations selected based on GFP expression.…”
Section: Methodsmentioning
confidence: 99%
“…Cyclin E1 was mutated by site-directed mutagenesis as described (18). MDA-MB-468 cells expressing the ecotropic receptor (19) were infected with pMSCV-IRES-GFP retrovirus expressing cyclin E1 wildtype and mutants as described (20). Subpopulations with graded expression of GFP and cyclin proteins were separated by sterile FACS and matched populations selected based on GFP expression.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, $85% of ER-positive breast cancers express high levels of BCL-2 (Dawson et al, 2010) and, accordingly, venetoclax and navitoclax synergized with tamoxifen in inhibiting the growth of patient-derived xenografts in mice (Vaillant et al, 2013). MCL-1 inhibitors, such as S63845, were also shown to efficiently inhibit the growth of triple-negative as well as HER-2-positive breast cancers when combined with chemotherapy or HER2-targeted therapies (Kotschy et al, 2016;Leverson et al, 2015b;Merino et al, 2017;Xiao et al, 2015;Young et al, 2016). Neuroblastoma growth was attenuated by inhibition of either BCL-2 or MCL-1 (Bate-Eya et al, 2016;Tanos et al, 2016), and the combination of venetoclax with the aurora kinase A inhibitor MLN8237 achieved complete remission in a patientderived xenograft of MYCN-amplified neuroblastomas (Ham et al, 2016).…”
Section: Impact Of Combinations Of Bh3-mimetics With Standard-of-carementioning
confidence: 99%
“…MCL1 is a prosurvival gene and a member of the BCL2 family, which governs the intrinsic apoptotic pathway (33) and has been shown to be highly expressed in some breast cancers, playing an important role in patient response to antitubulin chemotherapeutics (34). MCL1 expression has been associated with metastasis in colorectal (35), gastric (36,37), and breast cancers (38)(39)(40). Our study also identified aberrations of several other genes or chromosome regions that were enriched in ER + breast cancer patients with versus those without lymph node metastasis, including gains of chr12q and chr20q and losses of chr1p and chr9p, most of whose copy number alteration (CNA) have not previously been associated with breast cancer metastasis ( Figure 6B).…”
Section: Patient Materials and Clinical Informationmentioning
confidence: 99%